PERAN GREEN ACCOUNTING DAN STRUKTUR MODAL DALAM MENINGKATKAN FINANCIAL PERFORMANCE - Zulfa Rosharlianti; Yustina Laia (Jurnal Proaksi, 2025)
Main Purpose - The purpose of this study is to study how green accounting and capital structure impact financial performance. Method - This study uses quantitative with an associative approach with the help of Eviews 12 software. For this study, the purposive sampling method was used to collect samples of 15 food & beverage sector companies for the 2019-2023 period with a total of 75 data observations. Main Findings - According to the analysis results, green accounting does not affect financial performance, but capital structure affects financial performance. In addition, this study shows that both green accounting and capital structure affect financial performance simultaneously. Theory and Practical Implications - The implementation of green accounting provides a positive image to stakeholders regarding the company's concern for the surrounding environment. This study can provide recommendations for companies to better identify and manage environmental costs associated with their operational activities in order to reduce the risk of fines and litigation. Novelty - This is a study that examines green accounting, capital structure and financial performance in food & beverage sector companies participating in the PROPER program of the Indonesian Ministry of Environment and Forestry for the 2019-2023 period.